Dynamics of machine and tractor units: yaw stability with asymmetrically attached semi-integral plough - G. S. Gorin; Z. A. Godzhaev; V. M. Golovach; V. A. Kuzmin (Сельскохозяйственные машины и технологии)
The conditions of maintenance of yaw stability of the undercarriage of a tractor with the blocked interaxial and inter-wheel drives at work with the asymmetrical traction load are observed. Fundamental principles of the mathematical theory of friction are used for definition of a pole of friction and the pivot centres of wheels. The friction pole is in close proximity to the centre of a contact patch of the most loaded rear wheel of a tractor. Course stability of the tractor is influenced by the longitudinal forces, external side negative forces caused by a bottom pitch in the cross plane, and positive ones, caused by the shift of traction loading. The main power characteristic of the plow which is symmetrically mounted to the tractor is force which is counted on the basis of forces operating in the plow bottom. For maintenance of course stability of the tractor in case of asymmetrical mounting of a plow to the tractor а positive side force directed to the center of speeds should be applied in the joint. Opposite directed reaction is imposed on a plow for redistribution of side loads. The forces of asymmetric six-bodies plough, coordinates of the resulting forces in case of its assymetrical attachment are calculated. During the ploughing of a harvested field with a traction load of 40 kN, displased laterally by 1 m with the purpose of maintenance of directional stability, a lateral force of 2.7-3.5 kN should be applied to the tractor in the joint of attachment of semi-integral plough. At the same time a lateral force of 15.3 kN is applied to the front wheel, moving on furrow bottom.